Melting from an isothermal vertical wall. Synthesis of a numerical comparison exercise - Gobin, Dominique; Quéré, Patrick Le (Computer Assisted Methods in Engineering and Science, 2023)
This paper provides an analysis of the results of a comparison exercise on the numerical 2D solution of melting from a vertical wall, dominated by natural convection in the liquid phase. The thirteen contributions to this exercise cover the great variety of mathematical models and numerical procedures most commonly used in this field. The main conclusions presented at the AMIF Workshop (PCC99) held in Warsaw in June 1999 and at the Moving Boundaries Seminar in Ljubljana are summarized in the paper. They emphasize the need for the definition of such reference validation tests.